2023
DOI: 10.3390/nu15092061
|View full text |Cite
|
Sign up to set email alerts
|

Classroom-Based Physical Activity as a Means to Improve Self-Efficacy and Academic Achievement among Normal-Weight and Overweight Youth

Abstract: Although physical activity has positive physical and mental health outcomes, particularly among adolescents, a significant percentage of young people maintain a largely sedentary lifestyle. Considering that the youths spend the greater part of the day at school, this is considered an ideal setting to foster active and healthy living. Consequently, this study is intended to investigate the connection between physical activity, self-efficacy and academic achievement in normal-weight and overweight adolescents. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 92 publications
0
5
0
Order By: Relevance
“…In fact, motor activity is able to trigger a cascade of neurochemical growth factors capable of changing the entire brain's structure. This reflects the brain's ability to adapt to the various cognitive challenges it faces [136,137]. However, until recently, the relationship between intensive exercise and cognitive function was not entirely established, in light of the fact that the literature on the subject seemed to provide somewhat contradictory results.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, motor activity is able to trigger a cascade of neurochemical growth factors capable of changing the entire brain's structure. This reflects the brain's ability to adapt to the various cognitive challenges it faces [136,137]. However, until recently, the relationship between intensive exercise and cognitive function was not entirely established, in light of the fact that the literature on the subject seemed to provide somewhat contradictory results.…”
Section: Discussionmentioning
confidence: 99%
“…Low frustration experienced in different physical activity contexts (i.e., physical education and leisure-time physical activity) reports high well-being and enjoyment (Warburton et al, 2020), which would equip students with enhanced resilience. Success in physical activity also contributes to an increased sense of self-efficacy among students (Latino et al, 2023), a critical element of resilience. This heightened self-belief empowers students, reinforcing their confidence in academic pursuits (Komarraju and Nadler, 2013) and fostering a positive learning attitude and adaptability (Zimmerman, 2000), thus facilitating their adaptation to the school environment (Nowland and Qualter, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…By enhancing self-efficacy in learning, academic performance can be improved. Latino et al (2023) implemented a physical activity program during breaks to artificially intervene, and found that after 12 weeks, the attention and self-efficacy of most students had significantly improved. Du et al (2022) believes that students who achieve success in learning follow a learning pattern consisting of "before-class, in-class, and after-class" behaviors, which has been verified.…”
Section: Introductionmentioning
confidence: 99%